2004
DOI: 10.1100/tsw.2004.33
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Abundance and Seasonality of Insects in the Siruvani Forest of Western Ghats, Nilgiri Biosphere Reserve, Southern India

Abstract: The seasonal abundance patterns of insects inhabiting the understory vegetation of a mixed deciduous forest were examined with the help of the sweep-net sampling method. During the study period of 2 years, insects were sampled regularly from the understory vegetation of the three selected habitats (moist-deciduous, riverine, and teak plantation) of the mixed deciduous forest. Insect abundance was maximum in the moist-deciduous habitat and minimum in the teak plantation. Generally, insect abundance was the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…The peak of species richness and abundance of butterflies was recorded in the month of November and December. Researchers reported the similar findings of lycaenid abundance (Kunte 1997, Arun 2000, Arun and Vijayan 2004, Mathew and Anto 2007, Tiple and Khurad 2009, Hussain et al 2011, Akand 2012, Akand et al 2015b. Temporal changes in the abundance of lycaenid butterflies can be related to the adult food sources (Hill 1992).…”
Section: Relative Humiditymentioning
confidence: 65%
See 1 more Smart Citation
“…The peak of species richness and abundance of butterflies was recorded in the month of November and December. Researchers reported the similar findings of lycaenid abundance (Kunte 1997, Arun 2000, Arun and Vijayan 2004, Mathew and Anto 2007, Tiple and Khurad 2009, Hussain et al 2011, Akand 2012, Akand et al 2015b. Temporal changes in the abundance of lycaenid butterflies can be related to the adult food sources (Hill 1992).…”
Section: Relative Humiditymentioning
confidence: 65%
“…But this phenomenon was altered in the years (2015, 2016 and 2017) among habitats. The temporal fluctuations in abundance are an important manifestation of populations" response to the environmental conditions (Arun and Vijayan 2004). Such seasonal variation in the abundance of a species is an adaptive phenomenon evolved through evolution to take maximum advantage from the ambient environmental conditions (Arun 2000).…”
Section: Resultsmentioning
confidence: 99%
“…We believe this assumption to be reasonable because it is based on empirical observations from previous studies in the same study area (Brandt and Cresswell , Molokwu et al , ). Furthermore, insect abundance is generally lower in the dry season as in other seasonal tropical environments (Frith and Frith , Arun and Vijayan , Silva et al ) so that parents may work harder to raise young when they breed during the dry season. Moreover, differences in precipitation (Supplementary material Appendix 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wolda (1988) mentioned that in the tropical regions, changes in temperature were minimal and could not affect the seasonality of the insects during the year. However, Arun & Vijayan (2004) who studied the influence of five climate factors on insect populations in the South of India concluded that only the minimum temperature was correlated to monthly variation in species abundance. Intachat et al.…”
Section: Discussionmentioning
confidence: 99%